1979
DOI: 10.1113/jphysiol.1979.sp013017
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial transport pathways of rat colon determined in vivo by impulse response analysis.

Abstract: SUMMARY1. A method is described for studying transepithelial pathways for the movement of different solutes and water. Using the blood and the secretary curves of changing tracer activity following an intravenous bolus, the rate of transit of molecules together with their impulse response functions, which reflect the transfer processes, can be examined.2. Movements of Na, Cl, I, urea and water from blood to lumen across rat colonic epithelium were all consistent with simple diffusion through a paracellular rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
4
12
0
Order By: Relevance
“…To see how active Na absorption was affected, the flux ratio equation (Ussing, 1952) was used to estimate the passive component of the flux, JP5. Previous studies (Edmonds & Smith, 1979) (Table 2). In the adrenalectomized rats, active Na absorption, like the p.d., was unaffected by amiloride.…”
Section: Influence Of Luminal Na Concentration and Kmentioning
confidence: 92%
See 1 more Smart Citation
“…To see how active Na absorption was affected, the flux ratio equation (Ussing, 1952) was used to estimate the passive component of the flux, JP5. Previous studies (Edmonds & Smith, 1979) (Table 2). In the adrenalectomized rats, active Na absorption, like the p.d., was unaffected by amiloride.…”
Section: Influence Of Luminal Na Concentration and Kmentioning
confidence: 92%
“…Recently presented evidence (Edmonds & Smith, 1979) indicated that K, unlike Na, Cl and various other ions, crosses the epithelium not only by the paracellular pathway but largely by a K-selective pathway (Fig. 5).…”
Section: Plasma-to-lumen K Fluxmentioning
confidence: 99%
“…The mucosa-to-serosa flux of inulin was even reported to be higher in the colon than in the small intestine [19]. Furthermore, urea is transported from the plasma into the lumen in rats, sheep and goats, and in a concentration-dependent way in the latter two animals [4,5]. Thus, the results are conflicting and some of the results are difficult to reconcile with the description of the colonic epithelium as being fairly tight.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it seems likely that the secreted potassium is largely derived from the abundant potassium contained in the epithelial cells (Wills & Biagi, 1982). Previous kinetic studies indicated that the secreted potassium came from a potassium pool with a relatively fast turnover, a finding consistent with the existence of an epithelial cell secreting mechanism (Edmonds & Smith, 1979). Using 86 Rb+ as an analogue of potassium we have, therefore, in the present work also examined the origin of the secreted potassium, particularly in relation to the variable rates of potassium secretion.…”
Section: Introductionmentioning
confidence: 76%
“…Ordinarily in the distal colon, chloride appears to move from plasma to lumen by way of the paracellular route (Edmonds & Smith, 1979) and an increase of chloride permeability of the paracellular pathway could account for the observed rise of chloride secretion. That sodium movement into the colonic lumen was also increased in the rats on the normal diet lends some support to the possibility that the paracellular pathway had become more 'leaky ' during the infusion, to both sodium and chloride.…”
Section: Discussionmentioning
confidence: 99%